The Use of Solution-Focused Brief Therapy in Chinese Schools: A Qualitative Analysis of Practitioner Perceptions - Hong Chen; Xuanwen Liu; Samantha R Guz; Anao Zhang; Cynthia Franklin; Yingping Zhang; Yanzhou Qu (International Journal of School Social Work, 2018)
Solution-focused brief therapy (SFBT) is a strengthens-based, future-oriented approach that has received promising results over the past decade. Literature on SFBT has demonstrated the approach’s ability to meet the unique needs of various client populations while adapting to a variety of service delivery settings. Schools are a specific setting in which SFBT has been successfully utilized in the United States. With the growing popularity of SFBT, countries outside to the United States are beginning to implement SFBT in their schools. This article explored perceptions of the use of SFBT in schools amongst Chinese mental health practitioners. A survey was conducted by the Chinese government and included 134 participants. The qualitative results showed the Chinese practitioners have a strong interest in the strengths-based approach and feel that SFBT is culturally-adaptive to the Chinese student population. However, the practitioners are not confidently able to utilize SFBT techniques. The Chinese practitioners related the lack of confidence to a lack of SFBT focused training and professional develop opportunities. As SFBT research and practice continues to grow in China, the need for affordable, accessible SFBT trainings and supervision grows as well.
Keywords: solution-focused brief therapy; China; SFBT; school settings; qualitative analysis